Clinical, Biochemical, and Molecular Studies and Treatment of Pyridoxine-Dependent Epilepsy - J. Gordon Millichap (Pediatric Neurology Briefs Publishers, 2013)
Researchers at Autonomous University of Madrid, and other centers in Spain studied the clinical, biochemical, and genetic spectrum of pyridoxine-dependent epilepsy (PDE) in 12 patients with the clinically proven diagnosis.